Public support for emergency shelter housing interventions concerning stigmatized populations - Dum, Christopher P. (Criminology & public policy, 2017)
We examine citizen decision‐making in the context of providing access to safe housing to different noncriminal and criminal populations. More than 4,000 national online survey respondents considered different “emergency housing policy” scenarios that would affect the housing conditions of one of five randomly assigned populations of varying stigma (three noncriminal, two criminal). We find that the criminal populations had the least support for helpful housing policies and the most support for harmful housing policies. Furthermore, compared with a “no cost” policy, average support levels decreased when it increased taxes for the respondent.